Electrochemical Properties of Activated Carbon Electrodes for Supercapacitor Application: The Effect of Various Electrolyte Concentrations of Na2SO4 - rosi, Memoria; Fatmizal, M Nanang Ziad; Siburian, Dedy Hendra; Ismardi, Abrar; Abdullah, Nor Hakimin (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2023)
To achieve the high accomplishment of the supercapacitor, various electrolyte concentrations of Na2SO2 (0.5 M, 1 M, and 2 M) were added to the activated carbon (AC) electrode. The AC has a moderate surface area of 1,500 m2/g and a pore size of 1 nm (micropore scale). The AC electrode was deposited from the mixture of AC, carbon black, and polytetrafluoroethylene (PTFE) with a weight ratio of 8:1:1 using the doctor blade method. Cyclic Voltammetry (CV), Galvanostatic Charge Discharge (GCD), and Electrical Impedance Spectroscopy (EIS) were used to characterize the electrodes electrochemically. Based on CV, GCD, and EIS characterizations, the measured specific capacitance of 17.2 F/g and ESR of 4.4 W exhibit the best performance due to their high ionic conductivity. We can conclude that 2 M Na2SO4 is a viable option for the ionic electrolyte of the microporous AC for the high performance of a supercapacitor.